Faktor-Faktor yang Memengaruhi Niat UMKM Kuliner dalam Pemanfaatan Layanan Go-Food di Surakarta - Tampubolon, Novena Hasiani; Setyowati, Nuning; Adi, Raden Kunto (Agribusiness Department, Agriculture Faculty, Tanjungpura University, 2021)
This research aims to determine factors that influence the culinary MSMEs intention to use Go-Food in Surakarta using Technology Acceptance Model (TAM) modification. Factors are perceived resources, perceived usefulness, perceived ease of use, attitude towards using, and relative advantage. The basic research method is the descriptive method. The method of location determination is purposive. The method of sample determination is purposive sampling with many samples of 60 respondents. Data collection tools using questionnaires. The data analysis method is Structural Equation Modeling (SEM). Data analysis tools using Partial Least Square (PLS) with SmartPLS 3.0. software. The research results show that perceived resources have a positive effect on perceived usefulness and perceived ease of use, perceived usefulness and perceived ease of use have positive effects on attitude towards using, perceived usefulness and perceived ease of use have positive effects on relative advantage, attitude towards using and relative advantage have positive effects on behavior intention to use Go-Food in Surakarta.Keywords: Culinary MSMEs, Go-Food, Modified Technology Acceptance Model, Structural Equation Modeling